The Teachings of All Religions are Submission to God - Syarifah; Bambang Utomo (al-Afkar, Journal For Islamic Studies, 2024)
Tawakal is a work of the heart, a spiritual work, a worship whose meaning is very difficult, but needs to be applied in reality. Tawakal must be linked to the law of causes and causes, so that tawakal is no longer interpreted as silence without any activity. Tawakal will encourage someone to have a sense of optimism and courage in facing all life's problems. All these values exist in Islam, Christianity (Protestant and Catholic), Hinduism and Buddhism. The equal value of surrendering oneself to God is manifested in worship activities both alone and in congregation. In all religions it is the value of servitude in which there is the value of self-reliance.